Occupational hygiene in field farming - Olimovich, Kasimov Hayriddin; Serdanovna, Manasova Izimgul; Erkinovich, Nazarov Sulton; Jurayevna, Jumaeva Zukho; Hikmatovna, Nurova Zarnigor (International Journal of Psychosocial Rehabilitation, 2020)
This article aims to study the criteria for hygienic assessment of workers’ labor in the context of field farming. In field farming conditions, heavy physical labor can be affected by production factors such as dust, noise, vibration, exhaust fumes, sunlight in summer, cold temperatures in autumn and winter, mineral fertilizers and pesticides, vapors and gases. Therefore, the sanitary control of working conditions of workers in field farming is required to take into account the characteristics and factors of the production process.In this article, the goal of the study is a hygienic assessment of the working conditions of field workers